Composition of Micro-eukaryotes on the Skin of the Cascades Frog (Rana cascadae) and Patterns of Correlation between Skin Microbes and Batrachochytrium dendrobatidis - Kueneman, Jordan G.; Weiss, Sophie; McKenzie, Valerie J. (Frontiers in Microbiology, 2017)
Global amphibian decline linked to fungal pathogens has galvanized research on applied amphibian conservation. Skin-associated bacterial communities of amphibians have been shown to mediate fungal skin infections and the development of probiotic treatments with antifungal bacteria has become an emergent area of research. While exploring the role of protective bacteria has been a primary focus for amphibian conservation, we aim to expand and study the other microbes present in amphibian skin communities including fungi and other micro-eukaryotes. Here we characterize skin-associated bacteria and micro-eukaryotic diversity found across life stages of Cascades frog (Rana cascadae) and their associated aquatic environments using culture independent 16S and 18S rRNA marker-gene sequencing. Individuals of various life stages of Cascades frogs were sampled from a population located in the Trinity Alps in northern California during an epidemic of the chytrid fungus, Batrachochytrium dendrobatidis (Bd). We filtered the bacterial sequences against a published database of bacteria known to inhibit Bd in co-culture to estimate the proportion of the skin bacterial community that is likely to provide defense against Bd. Tadpoles had a significantly higher proportion of Bd-inhibitory bacterial sequence matches relative to subadult and adult Cascades frogs. We applied a network analysis to examine patterns of correlation between bacterial taxa and Bd, as well as micro-eukaryotic taxa and Bd. Combined with the published database of bacteria known to inhibit Bd, we used the network analysis to identify bacteria that negatively correlated with Bd and thus could be good probiotic candidates in the Cascades frog system.